A Note on Fractional Double Natural Transform - Maryam Omran (AlQalam Journal of Medical and Applied Sciences, 2022)
In this article, we present a definition of fractional double Natural transform of order α, 0<α≤1, for fractional differentiable functions. Some essential properties of fractional double Natural transform are determined. Furthermore, we set a relation between fractional double Natural transform and fractional double Laplace, fractional double Sumudu transforms.